2009
DOI: 10.1007/s10517-010-0802-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent Analysis of Connexin-43 Using Monoclonal Antibodies to Its Extracellular Domain

Abstract: Immunofluorescent analysis of connexin-43 was carried out on preparations of fixed and living cultures of rat and human glioma cells, HEK293 cells, and frozen sections of the rat brain with experimental glioma using monoclonal antibodies to recombinant extracellular fragment of connexin-43 (E2 second extracellular loop). These monoclonal antibodies visualized membrane and cytoplasmic pools of connexin-43 in preparations fixed with paraformaldehyde. Incubation of monoclonal antibodies to E2 extracellular loop w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…This assumption is also supported by rapid development of glioma in rats treated with NG/CDDP and IgG-NG/CDDP than that from CDDP group, as determined by morphometric analysis (Figure 6). To increase the efficiency of drug delivery to the glioma, nanogels were conjugated with mAbs against the targeted proteins Cx43 and BSAT1, which are highly expressed in tumor and peritumoral area (Baklaushev et al, 2009;Oliveira et al, 2005;Baklaushev et al, 2011Baklaushev et al, , 2012Yusubalieva et al, 2012). MRI data confirmed that this approach significantly decreased the tumor growth (Figure 7).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This assumption is also supported by rapid development of glioma in rats treated with NG/CDDP and IgG-NG/CDDP than that from CDDP group, as determined by morphometric analysis (Figure 6). To increase the efficiency of drug delivery to the glioma, nanogels were conjugated with mAbs against the targeted proteins Cx43 and BSAT1, which are highly expressed in tumor and peritumoral area (Baklaushev et al, 2009;Oliveira et al, 2005;Baklaushev et al, 2011Baklaushev et al, , 2012Yusubalieva et al, 2012). MRI data confirmed that this approach significantly decreased the tumor growth (Figure 7).…”
Section: Discussionmentioning
confidence: 84%
“…Amicon YM-30 centrifugal filters (MWCO 30 kDa), 1,2-ethylenediamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), ethylenediaminetetraacetic acid (EDTA), 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), cis-dichlorodiamminoplatinum (II) (cisplatin, CDDP) and other chemicals were from Sigma-Aldrich (St Louis, MO, USA). Anti-Cx43 and anti-BSAT1 monoclonal antibodies (Mw 150 kDa) were obtained as described earlier (Baklaushev et al, 2009. Fetal bovine serum (FBS), RPMI 1640 medium, penicillin, streptomycin, Trypsine-EDTA (0.5% trypsin, 5.3 mM EDTA tetrasodium salt), Alexa Fluor 488 goat anti-mouse IgG and other were from Invitrogen (Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid cells producing MAbE2Cx43 were previously obtained by us [2]. Aliquots of hybrid cells (3-5×10 6 ) from the cryobank were defrosted and injected intraperitoneally to BALB/c mice.…”
Section: Methodsmentioning
confidence: 99%